Association between physical fitness and musculoskeletal health in firefighters - Ras, Jaron; Soteriades, Elpidoforos S.; Smith, Denise L.; Kengne, Andre P.; Leach, Lloyd (Frontiers in Physiology, 2023)
Introduction: Firefighters are often placed in situations that require high levels of physical exertion leading to significant strain on firefighters' musculoskeletal system, predisposing them to musculoskeletal discomfort (MSD) and/or musculoskeletal injury (MSI). Physical fitness programmes are often recommended and justified, in part, to prevent injuries. The aim of this study was to determine the association between physical fitness and musculoskeletal health (MSH) in firefighters.Methods: In all 308 full-time firefighters took part in the study conducted in Cape Town, South Africa. Physical fitness tests encompassed a non-exercise estimation for cardiorespiratory fitness, grip and leg strength for upper and lower body strength, push-ups and sit-ups for muscular endurance, and sit-andreach for flexibility. The Nordic Musculoskeletal Questionnaire and Cornell Musculoskeletal Discomfort Questionnaire were used to determine MSIs and MSD, respectively. A p-value <0.05 indicated statistical significance.Results: Every one unit increase in AbV ̇O2max, push-ups, sit-ups and sit-and-reach decreased the odds of firefighters reporting MSIs by 5% (p=0.005), 3% (p=0.017), 3% (p=0.006) and 3% (p=0.034), respectively. Every one repetition increase in push-up capacity increased the odds of reporting neck, elbow and forearm, wrist and hand, and thigh discomfort by 3% (p=0.039), 4% (p=0.031), 5% (p=0.002) and 5%` (p=0.007), respectively. Every one repetition increase in sit-ups capacity increased the odds of firefighters reporting upper back discomfort and thigh discomfort by 5% (p=0.045) and 7% (p = 0.013), respectively.Maintenance of physical fitness is likely beneficial in reducing MSIs, however, may increase the feeling of MSD in firefighters. In addition, it may be that there is an ideal level of physical fitness that is conducive to the reduction of MSIs and should be further studied.